Pengaruh Penerapan Sistem Bagi Hasil Syariah terhadap Kinerja Koperasi Berbasis Balanced Scorecard dengan Komitmen Organisasi sebagai Variabel Moderasi - Zulkarnaini, Zulkarnaini; Lakharis Inuzula; Zulfikar Zulfikar; Kheriah Kheriah; Julia Alfianti; Mariana Mariana (Journal of Islamic Management, 2025)
This study investigates the implementation of cooperative performance measurement using the Balanced Scorecard (BSC) framework, with a specific focus on the influence of the Sharia-based profit-sharing system and the moderating role of organizational commitment. Drawing on a sample of 33 Sharia-based cooperatives in Lhokseumawe, the study employs multiple linear regression and Moderated Regression Analysis (MRA) to test the proposed model. The findings reveal a significant positive impact of the Sharia-based profit-sharing system on BSC-based performance (path coefficient = 0.573; p < 0.001), as well as a strong influence of organizational commitment (path coefficient = 0.568; p < 0.001). Notably, the interaction effect between profit-sharing and organizational commitment is also significant (path coefficient = 0.107; p = 0.004), indicating that high organizational commitment enhances the effectiveness of Sharia-compliant systems in driving BSC performance. This research contributes to the limited body of literature that integrates Islamic financial principles with strategic performance frameworks, offering a novel perspective on how religious-based financial systems can be synergized with modern management tools to improve cooperative performance.